Use of oral antihypertensive medication preceding blood pressure elevation in hospitalized patients - Macedo,Cristiano Ricardo Bastos de (2001)
OBJECTIVE: To evaluate the frequency of oral antihypertensive medication preceding the increase in blood pressure in patients in a university hospital, the drug of choice, and the maintained use of antihypertensive medication. METHODS: Data from January to June 1997 from the University Hospital Professor Edgard Santos Pharmacy concerning the prescriptions of all inpatients were used. Variables included in the analysis were: antihypertensive medication prescription preceding increase in blood pressure, type of antihypertensive medication, gender, clinical or surgical wards, and the presence of maintained antihypertensive medication. RESULTS: The hospital admitted 2,532 patients, 1,468 in surgical wards and 818 in medical wards. Antihypertensive medication prescription preceding pressure increase was observed in 578 patients (22.8%). Nifedipine was used in 553 (95.7%) and captopril in 25 (4.3%). In 50.7% of patients, prescription of antihypertensive medication was not associated with maintained antihypertensive medication. Prescription of antihypertensive drugs preceding elevation of blood pressure was significantly (p<0.001) more frequent on the surgical floor (27.5%; 405/1468) than on the medical floor (14.3%; 117/818). The frequency of prescription of antihypertensive drugs preceding elevation of blood pressure without maintained antihypertensive drugs and the ratio between the number of prescriptions of nifedipine and captopril were greater in surgical wards. CONCLUSION: The use of antihypertensive medication, preceding elevation of blood pressure (22.8%) observed in admitted patients is not supported by scientific evidence. The high frequency of this practice may be even greater in nonuniversity hospitals.